Anesthesia: Principles, Clinical Practice, and Recent Advances - George , Steve (CoinReads Media Prima, 2025)
Anesthesia is a fundamental component of modern surgical and interventional care, enabling procedures to be performed safely and humanely through the achievement of analgesia, hypnosis, amnesia, and appropriate muscle relaxation, while maintaining physiological homeostasis. Contemporary anesthetic practice extends beyond drug administration to encompass comprehensive perioperative management, including pre-anesthetic risk assessment, intraoperative monitoring, airway management, and postoperative recovery care. Advances in anesthetic pharmacology, monitoring technologies, and equipment design have substantially improved patient safety and expanded the scope of anesthesia across diverse clinical settings, including ambulatory surgery, non-operating room anesthesia, and critical care. The selection of anesthetic techniques, ranging from general, neuraxial, and regional anesthesia to monitored anesthesia care, is increasingly individualized and guided by surgical requirements, patient comorbidities, functional status, and patient preferences. Innovations such as ultrasound-guided regional anesthesia, multimodal analgesia, processed electroencephalographic monitoring, and enhanced recovery pathways have further optimized perioperative outcomes while reducing complications and resource utilization costs. In parallel, the implementation of standardized safety protocols, improved communication strategies, and system-based approaches have contributed to a marked decline in anesthesia-related morbidity and mortality. This review provides an integrated overview of the core principles of anesthesia, current clinical practices, and recent advances that continue to shape the evolution of anesthesiology toward a safer, more precise, and patient-centered perioperative care.